Cardiovascular risk following cannabinoid treatment for patients with chronic pain. (3rd October 2022) - Holt, A; Strange, J E; Rasmussen, P V; Blanche, P; Nouhravesh, N; Jensen, M H; Schjerning, A M; Schou, M; Torp-Pedersen, C; Gislason, G H; Hansen, M L; McGettigan, P; et al.
Abstract: Background: Treatment with medical cannabis for chronic pain is in popular demand, and a rising number of countries allow physicians to prescribe medical cannabis for pain management. However, data on drug-safety is scarce. Studies have showed a risk of cardiovascular side effects following use of recreational cannabis warranting further investigations into the safety of prescribing medical cannabis. Purpose: We investigated risk of new-onset arrhythmias (tachy- or bradyarrhythmia and conduction disorders), acute coronary syndrome (ACS) and heart failure (HF) following use of prescribed medical cannabis compared with no use in a nationwide cohort of patients with chronic pain. Methods: Using nationwide Danish registers, a cohort of patients with chronic pain and without prior history of arrhythmias, ACS, HF or prescribed medical cannabis (cannabinoid, cannabidiol or dronabinol) use were followed from 2018–2021. Any patient from the cohort initiating first-time treatment with medical cannabis was identified and matched 1:10 to corresponding controls within the cohort using incidence density sampling. Matching parameters were age group, sex, and chronic pain diagnosis. Follow-up was initiated at the date of the first claimed prescription of medical cannabis or the corresponding date among controls. We reported 180-day standardized absolute risks (AR) with 95% confidence intervals (CI) and risk ratios (RR) from fitted multivariable logistic regression models comparing patients exposed to medical cannabis with patients not exposed. Separate analyses for each chronic pain group were conducted as well. Results: Among 1.6 million patients with chronic pain, 4, 562 patients claimed at least one prescription of medical cannabis (exposed) and were each matched to 10 controls (non-exposed). Exposed and non-exposed patients were identical in relation to matching parameters; however, exposed patients were slightly more comorbid, and a larger proportion was concomitantly treated with other pain medication (Table). The risk of new-onset arrhythmia was elevated among exposed patients with 180-day AR of 0.71% (95% CI 0.47%–0.94%) compared with 0.43% (95% CI 0.37%–0.49%) yielding a RR of 1.64 (95% CI 1.04–2.23). The risk of new-onset ACS and HF was not increased comparing exposed to non-exposed with corresponding 180-day ARs of 0.13% (95% CI 0.03%-0.23%) vs 0.11% (95% CI 0.08%–0.14% and 0.13% (95% CI 0.03%–0.24%) vs 0.14% (95% CI 0.11%–0.17% (corresponding RRs of 1.2 [95% CI 0.3–2.1] and 0.9 [95% CI 0.2–1.7]) (Figure). Subgroup analyses of each chronic pain group yielded similar results. Conclusion: In a nationwide cohort of patients with chronic pain, use of medical cannabis was associated with a 64% risk increase of arrhythmias compared with no use. This poses a potential health concern and is vital knowledge for any physician prescribing medical cannabis. Use of medical cannabis was not associated with an elevated risk of ACS or HF. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Ib Mogens Kristiansens Almene FondHelsefonden